Radiology of Parasitic Diseases : A Practical Approach - LI, Hongjun (Springer Netherlands : Imprint: Springer, 2017)
This book primarily summarizes the imaging characteristics and theory of parasitic disease, offering a clinical guide and practical approach to understanding, preventing and diagnosing parasitic disease. Through imaging diagnosis and cross-research of imaging with autopsy and pathology, it highlights the chief characteristics and evolution of imaging, which provides primary scientific data for the understanding and research of parasitic disease. Divided into 9 chapters, this volume is fully illustrated with DR, CT and MRI images of different kinds of parasitic diseases, providing a valuable resource for radiologists in this field. Li Hongjun, is a Professor and Director of the Diagnostic radiology Department in Beijing You An Hospital, affiliated with Capital Medical University, Beijing, China.
Keywords: Medicine.; Parasitology.; Radiology.; Infectious diseases.; elektronické knihy; electronic books